Thermal comfort perception among park users in Prague, Central Europe on hot summer days-A comparison of thermal indices - Kirschner, Vlaďka; Urban, Aleš; Chlapcová, Lucie; Řezáčová, Veronika (PloS one, 2025)
The assessment of human perception of the thermal environment is becoming highly relevant in the context of global climate change and its impact on public health. In this study, we aimed to evaluate the suitability of the use of four frequently used thermal comfort indices (thermal indices)-Wet Bulb Global Temperature (WGBT), Heat Index (HI), Physiologically Equivalent Temperature (PET), and Universal Thermal Climate Index (UTCI)-to assess human thermal comfort perception in three large urban parks in Central Europe, using Prague, the capital of the Czech Republic, as a case study. We investigated the relationship between the four indices and the thermal perception of park visitors, while taking into account the effect of the sex, age, and activity of the respondents and the week-time and daytime of their visit (assessed parameters). Park visitors were interviewed during the summertime, while collecting meteorological data. The correlations were performed to explore the relationship between the thermal perception and the individual thermal indices, multivariate statistical methods were used to explain how well the variation in thermal perception can be explained by the assessed parameters. We found a significant association between all the indices and thermal perception; however, the relationship was the strongest with HI. While thermal perception was independent of sex and week-time, we found a significant effect of age, physical activity, and daytime of the visit. Nevertheless, the effects can largely be explained by thermal conditions. Based on the results, we conclude that all the investigated indices are suitable for use in studies of thermal comfort in parks in Central Europe in summertime, while HI seems the most suitable for architects and planners.
Keywords: senioři; Seasons; veřejné parky; mladiství; Česká republika; Thermosensing; Middle Aged; vysoká teplota; percepce; mužské pohlaví; Adult; mladý dospělý; Czech Republic; Young Adult; vnímání teploty; ženské pohlaví; Humans; lidé středního věku; Hot Temperature; Perception; dospělí; Female; Aged; Parks, Recreational; roční období; Adolescent; lidé; Male